Pengaruh Permainan Lompat Tali Irama terhadap Perkembangan Motorik Kasar Anak 4-5 Tahun Taman Kanak-Kanak Kemala Bhayangkari - Indah Juniarti; Vivi Anggraini (Lembaga Yasin AlSys, 2026)
Gross motor development in early childhood is important because it forms the foundation for locomotor skills, coordination, and balance, while studies that specifically examine the implementation of a rhythm-based rope-jumping game with jump heights safely modified for children aged 4–5 years in the context of kindergarten learning remain limited. This study aimed to analyze the effect of a rhythmic rope-jumping game on the gross motor development of children aged 4–5 years at Kemala Bhayangkari Kindergarten. The study employed a quantitative approach with a quasi-experimental nonequivalent control group design, involving 20 children consisting of 10 children in the experimental class and 10 children in the control class selected through purposive sampling. Data were collected using performance tests and checklist-based observations of gross motor indicators covering movement in rhythm, coordination, balance, and agility, and were then analyzed through prerequisite tests of normality and homogeneity, followed by an independent-samples t-test and Cohen’s d effect size. The results showed a significant difference between the experimental and control groups (sig. 2-tailed = 0.013), with a higher increase in the mean score in the experimental class, rising from 10.0 to 14.0, compared with the control class, which increased from 9.8 to 12.4, and demonstrated a very strong effect size (d = 2.05). These findings confirm that rhythm-based play activities can be an effective strategy for optimizing children’s gross motor development. Therefore, kindergarten teachers are advised to integrate rhythmic rope-jumping games gradually and safely into classroom learning. The implications of this study include a theoretical contribution to the literature on play-based learning and practical implications for early childhood education and kindergarten institutions, while also opening opportunities for further research on intervention duration and the generalizability of findings across more diverse school contexts.